PENENTUAN PRIORITAS PENINGKATAN PENERANGAN JALAN UMUM DI KELURAHAN KOYA BARAT DISTRIK MUARA TAMI KOTA JAYAPURA - Herry Wijaya; Harmonis Rante; Dewi Ana Rusim (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
After the Youtefa Bridge was built and operated, the travel time to Muara Tami District, especially Koya Barat Village, was faster and impact to the increasing of population growth. This population growth has encouraged an increase in land transportation, but has not been matched by an increase in public street lighting infrastructure. The length of the road in the Koya Barat Village reaches 47.67 Km, the average width is 2.5 - 6 meters, with the function of the road as a collector road. The length of the road that has been served by public street lighting is 1.6 Km or only 3.36% of the length of the segment in Koya Barat Village. The purpose of this study was to determine the priority of improving public street lighting services. Data collection is done by observation, documentation and through scientific publications. Data analysis was carried out quantitatively. The results showed that the order of priority for improving public street lighting services in the Koya Barat Village was Koya Barat Street, Lingkar Tengah Timur Kotim Street, Paniai Street, Lingkar Barat Kotim Street, Jalur II Street, Jalur I Street, Penghubung Koya Barat Street, Yapen Street, Manokwari Street, Jayapura Street, Timika Street, Jayawijaya Street, Wamena Street, Swakarsa Street, Nabire II Street, Merauke Street, Nabire Street, Sorong Street, Skouw Sae Street, Biak Street, Baring-Baring Street, Muara Tami Street, Fak-fak Street, Gambut Street, Demba Street, Lele Street, Penghubung III Street, Bridge II Street, Nabire I Street, Penghubung II Street, TPU Koya Barat Street, Muara Tami Street, Balai Benih Ikan Street and Kompleks Tentara Street..